CLINICAL PHARMACOLOGY OF ANTIHYPERTENSIVE DRUGS IN PREGNANT WOMEN - Bazarova Albina Mukhammadjonovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article discusses the clinical pharmacology of antihypertensive drugs in pregnant women, focusing on the physiological and pharmacokinetic alterations of pregnancy, the safety and efficacy of commonly used antihypertensive agents, and the rationale behind therapeutic choices. Hypertensive disorders during pregnancy — including chronic hypertension, gestational hypertension, and preeclampsia — represent a major cause of maternal and perinatal morbidity and mortality worldwide. The paper analyzes the mechanisms of drug action, placental transfer, fetal risks, and clinical decision-making principles involved in antihypertensive therapy during pregnancy. Evidence-based recommendations are presented for the use of methyldopa, labetalol, and nifedipine as first-line agents, while drugs such as ACE inhibitors and angiotensin receptor blockers are reviewed for their teratogenic potential.